Endoscopic shielding technique with a newly developed hydrogel to prevent thermal injury in two experimental models. Issue 6 (24th April 2017) - Lorenzo‐Zúñiga, Vicente; Boix, Jaume; Moreno de Vega, Vicente; Bon, Ignacio; Marín, Ingrid; Bartolí, Ramón
Abstract : Background and Aim: A newly developed hydrogel, applied through the endoscope as an endoscopic shielding technique (EndoSTech), is aimed to prevent deep thermal injury and to accelerate the healing process of colonic induced ulcers after therapeutic endoscopy. Methods: Lesions were performed in rats ( n  = 24) and pigs ( n  = 8). Rats were randomized to receive EndoSTech (eight rats each) with: saline (control), hyaluronic acid and product. In pigs, three ulcer sites were produced in each pig: endoscopic mucosal resection (EMR)‐ulcer with prior saline injection (A; EMR‐saline), EMR‐saline plus EndoSTech with product (B; EMR‐saline‐P), and EMR with prior injection of product plus EndoSTech‐P (C; EMR‐P‐P). At the end of the 14‐day study, the same lesions were performed again in healthy mucosa to assess acute injury. Animals were sacrificed after 7 (rats) and 14 (pigs) days. Ulcers were macroscopically and histopathologically evaluated. Thermal injury (necrosis) was assessed with a 1‐4 scale. Results: In rats, treatment with product improved mucosal healing comparing with saline and hyaluronic acid (70% vs 30.3% and 47.2%; P  = 0.003), avoiding mortality (0% vs 50% and 25%; P  = 0.038), and perforation (0% vs 100% and 33.3%; P  = 0.02); respectively. In pigs, submucosal injection of product induced a marked trend towards a less deep thermal injury (C = 2.25‐0.46 vs A and B = 2.75‐0.46; P  = 0.127). Mucosal healing rate was higher with product (B = 90.2‐3.9%, C = 91.3‐5.5% vs A = 73.1‐12.6%; P  = 0.002). Conclusions: This new hydrogel demonstrates strong healing properties in preclinical models. In addition, submucosal injection of this product is able to avoid high thermal load of the gastrointestinal wall.